Characteristics of Bituminous Materials : Supplement to Bibliography No. 35 - Traxler, R.N; Schweyer, H.E (Highway Research Board, 1966)
This supplement comprises of 370 references prior to the year 1962. An autho index is also available with approximately 370 papers involved.